158k views
1 vote
The expression log (x^6y^3/z^9) can be written in the form Alog(x)+Blog(y)+Clog(z) where

A=
B=
C=

User Speksy
by
4.9k points

2 Answers

3 votes

Answer:

b

Explanation:

User Bernhard Schussek
by
5.4k points
5 votes

Answer:

A = 6

B = 3

C = 9

Explanation:

We start by using repeatedly the product rule of logarithms that converts the logarithm of a product of two factors into the addition of logarithms:
log (A*B)=log(A) + log(B):


log (x^6*y^3*z^9)= log (x^6*[y^3*z^9])=log(x^6)+log(y^3*z^9)=\\=log(x^6)+log(y^3)+log(z^9)

At this point we use on each term of the expression we found above, the power rule of logarithms that states:
log(A^m)=m*log(A)

This gives as:


log(x^6)+log(y^3)+log(z^9)=6*log(x)+3*log(y)+9*log(z)

Therefore, the coefficients A, B, and C requested are:

A = 6

B = 3

C = 9

User Gord Thompson
by
4.7k points